EXPLORING INTERCULTURAL VALUES FROM THE PERSPECTIVE OF WESTERN-ASIAN WAY OF LIFE -A STUDY OF LILTING FILM- - Widya Rizky Pratiwi (Journal of English Education, 2017)
People are not born with the genetic imprint of particular culture because it is the set of knowledge and behavior and the interpretation of both as habits acquired and learned by the members of society through interaction and socialization by using different media such as film.  Lilting is a film that presents the issue of cultural value. It is a British drama that cultivate a vibrant dynamic between Western way of life and Asian stories. This qualitative descriptive research focused on the exploration of intercultural values from the perspective of Western-Asian Way of Life to find out the differences among British, Chinese and Indonesian culture. Data were obtained from audio visual material of lilting film and other documents, e.g. newspaper and journal about lilting film. The techniques of data analysis were done by watching, writing some notes, data reduction, data display, and drawing conclusion. The result shows that lilting contains some cultural knowledge especially the difference of western and Asian way of life, language used by England and China, cultural biases (ethnocentric, stereotype, discrimination and prejudice), people’s perception about homosexual, the way people look at kissing in public place, the way to offer food, the way people speak up in direct conversation, the process of assimilation and acculturation to a new culture, the function of a professional translator, and the most important lesson of how difficult to communicate when we do not have little bit knowledge and information of other language and culture.